Impact of an accessory cavitated uterine mass on fertility: case presentation and review of the literature - Strug, Michael; Christmas, Abigail; Schoonover, Amanda; Romero, Vivian C.; Cordoba, Marcos; Leary, Elizabeth; Thakur, Mili (F&S Reports (Online), 2023)
We report a case of an accessory cavitated uterine mass (ACUM) in a patient with infertility and chronic pelvic pain. In addition, we summarize the literature to better characterize ACUM diagnosis and management. A comprehensive literature search using the PubMed database was performed through April 2023. Historical ACUM diagnostic criteria were applied as inclusion criteria. Descriptive statistics and statistical evaluation were reported. A 31-year-old nulligravid woman presented with chronic pelvic pain, dysmenorrhea, primary infertility, and history of endometriosis. Three-dimensional ultrasonography identified an ACUM and laparoscopic excision provided complete resolution of symptoms. Subsequently, she conceived without assistance twice with uncomplicated vaginal deliveries. A total of 154 articles were identified, 34 papers met inclusion criteria and were individually reviewed, consisting of 70 reported cases. The most common presenting complaints were dysmenorrhea (81.4%), chronic pelvic/abdominal pain (54.1%), and refractory pain (34.3%). Diagnostic imaging included magnetic resonance imaging (62.9%) and transvaginal ultrasound (55.7%). Management included resection via laparoscopy (75.7%) or laparotomy (18.6%), or hysterectomy (5.7%). Of cases with reported outcomes, 90.7% had complete relief of symptoms after surgery. ACUM often presents with dysmenorrhea, chronic pelvic pain, or abdominal pain and is identifiable on magnetic resonance imaging as a hyperenhancing mass. Three-dimensional transvaginal ultrasound can also accurately identify ACUM. A total of 90.7% of patients had complete relief of symptoms after intervention. It is important to identify ACUM early to relieve pain and reduce unnecessary interventions. Like our patient, other reports have demonstrated concomitant infertility and endometriosis. However, further investigation is needed to explore the association between infertility and ACUM.